Phosphine-free, low-temperature synthesis of tetrapod-shaped CdS and its hybrid with Au nanoparticles - Du, Yaping (2014)
Tetrapod-shaped CdS colloidal nanocrystals are synthesized using a facile, phosphine-free synthesis approach at low temperature. The arm length and diameter of CdS tetrapods can be easily tuned by using different source of sulphureous precursors, i.e., sulfur powder, thioacetamide, and sodium diethyldithiocarbamate. Moreover, the growth of Au nanoparticles onto CdS to form metal–semiconductor hybrid nanocrystals is also demonstrated. The tetrapod-shaped CdS nanocrystals exhibit strong arm-diameter-dependent absorption and photoluminescence characteristics. Importantly, the as-obtained CdS tetrapods exhibit promising photocatalytic activity for the water-splitting reaction in photoelectrochemical cells.